2005
DOI: 10.1302/0301-620x.87b9.16518
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the risk factors for the development of post-operative spinal epidural haematoma

Abstract: In order to identify the risk factors and the incidence of post-operative spinal epidural haematoma, we analysed the records of 14 932 patients undergoing spinal surgery between 1984 and 2002. Of these, 32 (0.2%) required re-operation within one week of the initial procedure and had an International Classification of Diseases (ICD)-9 code for haematoma complicating a procedure (998.12). As controls, we selected those who had undergone a procedure of equal complexity by the same surgeon but who had not develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
233
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(241 citation statements)
references
References 33 publications
5
233
0
3
Order By: Relevance
“…It is conceivable that spinal/epidural hematoma may occur in anticoagulated patients who are receiving regional anesthesia or analgesia. However, a recent study found that well-controlled anticoagulation was not associated with an increased risk of postoperative spinal/epidural hematoma [89]. …”
Section: Risk-reduction Interventionsmentioning
confidence: 99%
“…It is conceivable that spinal/epidural hematoma may occur in anticoagulated patients who are receiving regional anesthesia or analgesia. However, a recent study found that well-controlled anticoagulation was not associated with an increased risk of postoperative spinal/epidural hematoma [89]. …”
Section: Risk-reduction Interventionsmentioning
confidence: 99%
“…The quoted incidence of postoperative symptomatic epidural hematoma occurring after all spinal procedures requiring surgical intervention ranges from 0.2% to 2.9% [1,6,13]. Closed-suction drainage is believed effective in preventing these complications in spine surgery, but only a few studies have addressed the Each author certifies that he or she has no commercial associations (eg, consultancies, stock ownership, equity interest, patent/licensing arrangements, etc) that might pose a conflict of interest in connection with the submitted article.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative epidural hematoma as an early complication after decompression in lumbar stenosis occurs with a prevalence of 0.1-0.2% [1][2][3][4]. Magnetic resonance imaging (MRI) is recommended in patients with postoperative increasing pain and new neurological symptoms to rule out hematoma.…”
Section: Introductionmentioning
confidence: 99%